Zinc Treatment to Under-five Children: Applications to Improve Child Survival and Reduce Burden of Disease - Larson, Charles P; Roy, SK; Khan, Azharul Islam; Rahman, Ahmed Shafiqur; Qadri, Firdausi (Journal of Health, Population and Nutrition, 2009)
Zinc is an essential micronutrient associated with over 300 biological functions. Marginal zinc deficiency states are common among children living in poverty and exposed to diets either low in zinc or high in phytates that compromise zinc uptake. These children are at increased risk of morbidity due to infectious diseases, including diarrhoea and respiratory infection. Children aged less than five years (under-five children) and those exposed to zinc-deficient diets will benefit from either daily supplementation of zinc or a 10 to 14-day course of zinc treatment for an episode of acute diarrhoea. This includes less severe illness and a reduced likelihood of repeat episodes of diarrhoea. Given these findings, the World Health Organization/United Nations Children's Fund now recommend that all children with an acute diarrhoeal illness be treated with zinc, regardless of aetiology. ICDDR.B scientists have led the way in identifying the benefits of zinc. Now, in partnership with the Ministry of Health and Family Welfare, Government of Bangladesh and the private sector, the first national scaling up of zinc treatment has been carried out. Important challenges remain in terms of reaching the poorest families and those living in remote areas of Bangladesh. Key words: Child survival; Diarrhoea, Acute; Diarrhoea, Infantile; Interventions; Morbidity; Zinc; Zinc deficiency; Zinc therapy; Bangladesh doi:10.3329/jhpn.v26i3.1901 J Health Popul Nutr 2008 Sept:26(3): 356-365